The role of the nurse in supporting health and well-being for people with learning (intellectual) disabilities - Northway, Ruth (Henry Stewart Talks, 2017)
Understanding the nature of learning disabilities, Health needs of people with learning disabilities, Barriers to healthcare experienced by people with learning disabilities, The role of nurses in enhancing health & well-being of people with learning disabilities